MANAJEMEN PENINGKATAN PROFESIONALISME DOSEN DI PROVINSI BANTEN - Fauzi, Anis (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2013)
This article discusses the management of the improvement of lecturers' professionalism in Banten. There are some important research questions studied in thi  article:  (1)  what  are  the  aspects  in   manag ement   of  the  improvement  of lecturers' professionalism in Banten?; (2) How is the implementation of the improvement of lecturers' professionalism in Banten?; (3) What are the problems and weaknesess faced by the management of the improvement of ledurers'professionalism in Banten?; and (4) What are the steps that will be done by the management university in improving the lecturers' professionalism in Banten in the future? This research uses qualitative method. The descriptive study is used in analyzing the data. The data of this research are obtained from lecturers and university bureaucrats in The State Institute for Islamic Studies of IAIN ''SMH